The Regulatory Protein RosR Affects Rhizobium leguminosarum bv. trifolii Protein Profiles, Cell Surface Properties, and Symbiosis with Clover - Rachwał, Kamila; Boguszewska, Aleksandra; Kopcińska, Joanna; Karaś, Magdalena; Tchórzewski, Marek; Janczarek, Monika (Frontiers in Microbiology, 2016)
Rhizobium leguminosarum bv. trifolii is capable of establishing a symbiotic relationship with plants from the genus Trifolium. Previously, a regulatory protein encoded by rosR was identified and characterized in this bacterium. RosR possesses a Cys2-His2-type zinc finger motif and belongs to Ros/MucR family of rhizobial transcriptional regulators. Transcriptome profiling of the rosR mutant revealed a role of this protein in several cellular processes, including the synthesis of cell-surface components and polysaccharides, motility, and bacterial metabolism. Here, we show that a mutation in rosR resulted in considerable changes in R. leguminosarum bv. trifolii protein profiles. Extracellular, membrane, and periplasmic protein profiles of R. leguminosarum bv. trifolii wild type and the rosR mutant were examined, and proteins with substantially different abundances between these strains were identified. Compared with the wild type, extracellular fraction of the rosR mutant contained greater amounts of several proteins, including Ca2+-binding cadherin-like proteins, a RTX-like protein, autoaggregation protein RapA1, and flagellins FlaA and FlaB. In contrast, several proteins involved in the uptake of various substrates were less abundant in the mutant strain (DppA, BraC, and SfuA). In addition, differences were observed in membrane proteins of the mutant and wild-type strains, which mainly concerned various transport system components. Using atomic force microscopy imaging, we characterized the topography and surface properties of the rosR mutant and wild-type cells. We found that the mutation in rosR gene also affected surface properties of R. leguminosarum bv. trifolii. The mutant cells were significantly more hydrophobic than the wild-type cells, and their outer membrane was three times more permeable to the hydrophobic dye N-phenyl-1-naphthylamine. The mutation of rosR also caused defects in bacterial symbiotic interaction with clover plants. Compared with the wild type, the rosR mutant infected host plant roots much less effectively and its nodule occupation was disturbed. At the ultrastructural level, the most striking differences between the mutant and the wild-type nodules concerned the structure of infection threads, release of bacteria, and bacteroid differentiation. This confirms an essential role of RosR in establishment of successful symbiotic interaction of R. leguminosarum bv. trifolii with clover plants.